2019
DOI: 10.1177/0954405419844855
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive investigation of cutting mechanisms and hole quality in dry drilling woven aramid fibre–reinforced plastic with typical tools

Abstract: Due to high specific strength and strong toughness, aramid fibre–reinforced plastics have been widely used in the aircraft, military, and automobile industries. However, in the hole-making process, these excellent properties make aramid fibre–reinforced plastics difficult to machine and prone to severe entrance and exit damages. In this article, the cutting mechanisms of three typical tools (twist drill, burr tool, and brad drill) are thoroughly investigated during dry drilling of aramid fibre–reinforced plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The AFRP laminates used in this study are made of plain-woven aramid/epoxy prepregs with 60 vol% fiber fraction. The fabrication of the AFRP laminate follows the preciously established method [30]. More specifically, AFRP laminates were cured in an autoclave at 115°C for 60 min, and then at 180°C for 120 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AFRP laminates used in this study are made of plain-woven aramid/epoxy prepregs with 60 vol% fiber fraction. The fabrication of the AFRP laminate follows the preciously established method [30]. More specifically, AFRP laminates were cured in an autoclave at 115°C for 60 min, and then at 180°C for 120 min.…”
Section: Methodsmentioning
confidence: 99%
“…Dí az-Álvarez [29] compared the cutting performance of a brad drill and a twist drill during drilling of AFRP laminates and found that the brad drill can better suppress the delamination and fuzzing under low feed rates and high cutting speeds. Liu et al, further confirmed that the brad drill can effectively restrain the concession and deformation of aramid fibers and improve the shearing action of the cutting edge [30]. Despite the promising experimental results seen in drilling of AFRP deploying brad drills, the detailed delamination mechanism and the corresponding analytical model associated with such process are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…49 There are also studies in the literature showing that the brad drill produces the best hole quality in AFRP drilling due to the reduction in thrust and improvement in cutting action. 50 Push-out delamination, in contrast, occurs at the bottom surface of the drilled hole in a composite material. As the drill bit nears the hole exit, the thickness of the composite it needs to drill through becomes reduced.…”
Section: Delamination and Burr Formationmentioning
confidence: 99%
“…Similar research is in [2], which approached the problem by conducting systematic experiments to evaluate cutting performance and hole quality. Upon entering the holes, the cutting edges of the twist drill peel and tear the uncut material, resulting in severe fuzzing damage.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results indicated that the most significant effect was that the drill type influenced both the delamination factor and the surface roughness. All these articles [ 1 , 2 , 3 , 4 , 5 ] provide comprehensive and available information on the performance of tools for drilling aramid fiber-reinforced plastics, which can help guide process optimizations to achieve the desired hole quality.…”
Section: Introductionmentioning
confidence: 99%